Kelebihan Aplikasi Edmodo Dalam Pembelajaran Sejarah Di Sma Negeri 3 Bukittinggi - Rahmatul Atika Deswara; Zafri Zafri (Jurnal Kronologi, 2019)
Utilization of technology in the learning process encourages the creation of a variety of learning media that teachers can choose to use in effective learning. This is in accordance with Minister of Education and Culture Regulation No. 65 of 2013 which states that each teacher is required to apply information and communication technology in an integrated, systematic and effective manner. In formal and regular learning, it has implemented an online learning system created and used by educational institutions or institutions in the form of e-learning systems. One of the e-learning learning applications is the Edmodo application.This research uses a quantitative descriptive approach. The object of research that the writer will examine is the students of SMA Negeri 3 Bukittinggi, class XI IPS 2, who are registered in semester 1 of T.A 2019/2020. The instrument used was a Likert Scale model questionnaire. The data that has been collected is then scanned and the frequency is calculated.